1976
DOI: 10.1159/000231608
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Rabbit Homologous Skin Sensitizing Antibodies: IgE and a New Subclass IgG<sub>a</sub>

Abstract: Homologous skin sensitizing antibodies in the rabbit can be differentiated by their requirement for complement in expressing the passive cutaneous anaphylactic reaction as complement dependent (CD) or complement independent (CI). CI antibodies are representative of the IgE class, while the CD antibodies belong to a proposed new subclass of IgG designated IgGa (a = anaphylaxis). The following are characteristics of CI (IgE) antibodies: elution at 0.05 M on DEAE at pH 8.1, migration ahead of 7S in ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…In this study, heating to 56 °C had a dramatic effect on reaginic sheep serum. 90% of the PCA activity disappeared after 2-4 h. However, neat serum showed no reduction in PCA activity even after heating for 8 h. The reason for this is unclear but these results are similar to those obtained in rabbits [25,32]. Lindqvist [32], suggested a possible protective agent in reaginic sera; whereas Stux and Ovary [25] suggested that it may indicate a heat-stable subpopulation of IgE.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In this study, heating to 56 °C had a dramatic effect on reaginic sheep serum. 90% of the PCA activity disappeared after 2-4 h. However, neat serum showed no reduction in PCA activity even after heating for 8 h. The reason for this is unclear but these results are similar to those obtained in rabbits [25,32]. Lindqvist [32], suggested a possible protective agent in reaginic sera; whereas Stux and Ovary [25] suggested that it may indicate a heat-stable subpopulation of IgE.…”
Section: Discussionsupporting
confidence: 67%
“…It has also been induced by immuni zation with alum-precipitated human gamma-globulin [19], Short-term skin-sensitizing IgG antibody has also been reported after immunization with DNP-HGG [20], Immunoglobulin G with passive cutaneous anaphylaxis (PCA) activity has been defined in man [21], mouse [22], rat [23], guinea pig [24] and rabbit [25]. The PCA activity of IgG antibodies is not affected by heat and it does not re main in the skin for more than 1-3 days, except in the case of the guinea pig and rabbit [26], In these species IgG can remain in the skin for a week [25,27],…”
Section: Introductionmentioning
confidence: 99%
“…There was a heat-resistant component which is consistent with previous observations made with rabbit IgE (Revoltella & Ovary, 1969;Kravis & Zvaifler, 1974a;Stux & Ovary, 1976).…”
Section: Effect Of Heat Treatment On Ige Antibodysupporting
confidence: 91%
“…The likelihood that C5a was involved was small since the IgE antibody would not be expected to be complement fixing. Henson & Cochrane (1969) and Stux & Ovary (1976) both reported an anaphylactic IgG antibody in the rabbit which induced a PCA reaction that was dependent on an intact complement system. However, we could not find evidence for the existence of this antibody in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation